(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study aims to analyses the internalization of racial discourse in the novel and to examine how white supremacist ideologies shape the characters’ social cognition. Using Teun A. Van Dijk’s socio-cognitive approach in Critical Discourse Analysis and a qualitative descriptive method, the study identifies the discursive patterns that produce anticipatory fear before actual physical discrimination occurs. The results show that racial discourse deeply navigates the characters’ mental models, leading to the cognitive dehumanization of the ’Other’ and melancholia over lost racial privilege. Moreover, the characters build in-group boundaries and generate apocalyptic paranoia to rationalize victimization. These cognitive manipulations are frequently used to legitimize prejudice and conceal historical guilt. In conclusion, these results reveal how racism works most subtly at the cognitive level, showing that character’s experience racial anxiety even in the absence of real conflict, because they view the loss of whiteness as an existential threat rather than a biological phenomenon. Significantly, this study extends CDA research by demonstrating that dismantling white supremacy requires deconstructing not only institutional racism but also the invisible cognitive frameworks that sustain racial hierarchies in everyday life.